THE MEDIUM-SIZED CITY AND THE CHALLENGE OF REGIONAL AND SPATIAL DEVELOPMENT COMPETITIVENESS THE CASE OF CITIES IN TÉBESSA PROVINCE - Ghassir Imane; Zerieb Salah (International Journal of Innovative Technologies in Social Science, 2025)
Over the past three decades, Algeria’s urban network has undergone significant transformations driven by the economic and social changes that followed independence. These shifts have exacerbated disparities between major urban centers and smaller towns, which have faced marginalization and limited development. This study focuses on the developmental dynamics in medium-sized cities in Tébessa province, specifically the cities of Bir El-Ater (88,083 residents), El Ouenza (58,904 residents), and Cheria (82,369 residents), accounting for a combined population of 229,356 (34.02% of the urban system and 28.40% of the province’s total population according to PAW 20). The study highlights these cities’ potential for developing the industrial and agricultural sectors. Findings indicate that enhancing economic and social development in these cities could improve living conditions, curb migration to larger urban centers, and achieve balanced development. Achieving these goals requires strategic investment in local resources and infrastructure, focusing on water resources, agriculture, and manufacturing industries.